Better understanding the neurobiology of primary lateral sclerosis. (2nd November 2020) - Ozdinler, P. Hande; Gautam, Mukesh; Gozutok, Oge; Konrad, Csaba; Manfredi, Giovanni; Area Gomez, Estela; Mitsumoto, Hiroshi; Erb, Marcella L.; Tian, Zheng; Haase, Georg
Abstract: Primary lateral sclerosis (PLS) is a rare neurodegenerative disease characterized by progressive degeneration of upper motor neurons (UMNs). Recent studies shed new light onto the cellular events that are particularly important for UMN maintenance including intracellular trafficking, mitochondrial energy homeostasis and lipid metabolism. This review summarizes these advances including the role of Alsin as a gene linked to atypical forms of juvenile PLS, and discusses wider aspects of cellular pathology that have been observed in adult forms of PLS. The review further discusses the prospects of new transgenic upper motor neuron reporter mice, human stem cell-derived UMN cultures, cerebral organoids and non-human primates as future model systems to better understand and ultimately treat PLS.